2022
DOI: 10.1088/1741-2552/ac6537
|View full text |Cite
|
Sign up to set email alerts
|

The myokinetic stimulation interface: activation of proprioceptive neural responses with remotely actuated magnets implanted in rodent forelimb muscle

Abstract: Objective. Proprioception is the sense of one's position, orientation, and movement in space, and it is of fundamental importance for motor control. When proprioception is impaired or absent, motor execution becomes error-prone, leading to poorly coordinated movements. The kinaesthetic illusion, which creates perceptions of limb movement in humans through non-invasively applying vibrations to muscles or tendons, provides an avenue for studying and restoring the sense of joint movement (kinaesthesia). This tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
0
0
0
Order By: Relevance
“…[46] The adopted silicone phantom used in this study exhibited mechanical features comparable to those of the muscular tissue [48] and was already assessed in our previous study. [18] Based on our experience with animal tests, gained in vibrating magnets implanted in rodents' paws, [18] we found this methodology appropriate to test the system functionality and we do not expect significant performance deterioration in a real anatomical configuration in terms of tracking accuracy, precision, and frequency selectivity.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…[46] The adopted silicone phantom used in this study exhibited mechanical features comparable to those of the muscular tissue [48] and was already assessed in our previous study. [18] Based on our experience with animal tests, gained in vibrating magnets implanted in rodents' paws, [18] we found this methodology appropriate to test the system functionality and we do not expect significant performance deterioration in a real anatomical configuration in terms of tracking accuracy, precision, and frequency selectivity.…”
Section: Discussionmentioning
confidence: 99%
“…The outcomes from the video analysis test (Test A) confirmed the capability of the system in vibrating a moving magnet fixed onto a silicone phantom at the target frequency with a torsional efficiency always above 0.82, thus extending our previous studies that included static magnets only (Figure 4). [ 17,18 ] Moreover, the video analysis showed that the vibrations at 40 μNm led to magnet displacements up to ≈150 μm, which already demonstrated to be sufficient to elicit muscle sensory neural responses in an animal model. [ 18 ] These displacements are also comparable with those employed in some noninvasive studies to elicit kinesthetic illusions in targeted sensory reinnervated amputees.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations